2015
DOI: 10.1038/cddis.2014.571
|View full text |Cite
|
Sign up to set email alerts
|

A G-quadruplex DNA structure resolvase, RHAU, is essential for spermatogonia differentiation

Abstract: G-quadruplex (G4) DNA and G4 DNA resolvase are involved in a variety of biological processes. To understand the biological function of G4 DNA structures and their resolvases in spermatogenesis, we investigated the distribution of G4 structures in mouse testis and identified their alterations during spermatogenesis. Meanwhile, we studied the function of RNA helicase associated with AU-rich element (RHAU), a G4 DNA resolvase, in spermatogenesis with a germ-cell-specific knockout mouse model. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 68 publications
1
36
0
Order By: Relevance
“…In the previous study, we found that MS-275 stimulates bone formation by interaction with Dhx36, (13) also known for its critical roles in the process of cell proliferation. (38) Therefore, we deduced that Dhx36mediated signaling might be participating in highly triggered cell proliferative activity through MS-275 administration. Considering the significance of proliferation of osteoblast progenitor cells in the calvarial suture region during development, (29) it could be the critical distinction of MS-275 treatment toward CCD.…”
Section: Discussionmentioning
confidence: 98%
“…In the previous study, we found that MS-275 stimulates bone formation by interaction with Dhx36, (13) also known for its critical roles in the process of cell proliferation. (38) Therefore, we deduced that Dhx36mediated signaling might be participating in highly triggered cell proliferative activity through MS-275 administration. Considering the significance of proliferation of osteoblast progenitor cells in the calvarial suture region during development, (29) it could be the critical distinction of MS-275 treatment toward CCD.…”
Section: Discussionmentioning
confidence: 98%
“…RHAU helicase, also named G4 resolvase 1 (DHX36 gene product, or G4R1, from human) is a superfamily 2 DEAH-box helicase that plays a role in heart development (11), hematopoiesis (12) and spermatogenesis (13). RHAU was originally identified as a RNA helicase that binds RNA G4 with sub-nanomolar affinity (1417).…”
Section: Introductionmentioning
confidence: 99%
“…RHAU has also been shown to bind DNA G4 with similar affinity to RNA and can unfold DNA G4 (24), which also has crucial biological functions. In addition, a recent study revealed that RHAU directly binds to the DNA G4 structures formed on the promoter region of c-Kit , facilitating its expression and regulating spermatogonia differentiation (13). Sequence analysis showed that almost all metazoan species have RHAU orthologues (25).…”
Section: Introductionmentioning
confidence: 99%
“…DHX36 has been implicated as a regulator of RNA folding and assembly (17,18), RNA localization, translation (19), pre-mRNA processing (20), and transcription (21), most simply suggesting that it functions in both the cytoplasm and nucleus and interacts with both RNA and DNA G4s. Underscoring the importance of this protein and potentially G4s in vivo, DHX36 is an essential gene in mouse (22)(23)(24).…”
Section: ___________________________________mentioning
confidence: 99%